Use of topical mitomycin C in myoplasty of the medial rectus muscle of rabbits - Mamede, F. V.; Laus, J. L.; Cabral, V. P.; Vicenti, FAM; Barbieri-Neto, J. (Blackwell Publishing, 2004)
To possibly reduce postoperative adhesions that occur after ocular myoplasties, we investigated the topical effects of 0.04% mitomycin C on the repaired areas of the medial rectus muscle using an equine renal capsule preserved in 98% glycerin for reinforcement of the sutures. Twenty-four rabbits, divided into two groups of 12 animals each [untreated (control) and treated group (MMC)], were submitted to surgical rupture of the medial rectus muscle of one eye and repair of the defect 24 h later with sutures and an equine renal capsule. Post-operative prophylactic treatment of the two groups consisted of the administration of eye drops containing neomycin, polymyxin B and dexamethasone at regular 6-h intervals for eight consecutive days and daily rinsing with physiological saline. MMC animals received additional treatment with topical 0.04% mitomycin C every 6 h for 14 consecutive days. Slit lamp biomicroscopy showed greater irritation of the ocular surface in MMC animals during the first days post operatively. Adhesions were observed at 15 and 30 days of assessment in the two groups, but were more extensive in control animals at 60 days. Histopathology revealed inflammatory exudation in both groups, which was greater in MMC animals. Mitomycin C (0.04%) instilled at 6-h intervals for 14 consecutive days reduced the occurrence of fibrosis in the myoplastic areas. However, the equine renal capsule was found to be of little benefit for the reinforcement of myoplasties.
Keywords: Adhesion; equine renal capsule; extrinsic muscles; eye; mitomycin C; rabbit